Lebrikizumab Rapidly Lowers Inflammatory Biomarkers with Clinical Correlations in Moderate-to-Severe Atopic Dermatitis - Emma Guttman-Yassky; Zhe Sun; Laura Rebeca Mena; Nathan Hahn; Brian J. Nickoloff; Christoph Preuss; Kimberly Siu; Chitra R. Natalie; Gaia Gallo; Eric Wolf; Kilian Eyerich; Mònica Aparici; et al. (Dermatology and Therapy)
Abstract Introduction Lebrikizumab is a novel monoclonal antibody that selectively binds to interleukin (IL)-13 with high affinity and a slow dissociation rate. Methods We assayed serum from select patients enrolled in ADvocate1 and ADvocate2 to determine the impact of lebrikizumab on circulating biomarkers and pathways relevant to atopic dermatitis (AD) and to assess the correlation between key biomarkers and clinical measures of improvement. Results At baseline, IL-13, CC motif chemokine ligand (CCL)13, CCL17, CCL22, total immunoglobulin (Ig)E, IL-5, and periostin were elevated in patients with moderate-to-severe AD versus healthy controls (p < 0.001). Baseline Eczema and Area Severity Index (EASI) and Investigator’s Global Assessment (IGA) scores were significantly correlated with IL-13, IL-5, CCL13, CCL22, and CCL26. Lebrikizumab induced rapid and progressive reductions in CCL13, CCL17, CCL22, and periostin at weeks 4, 16, and 52 compared with baseline (p < 0.05). AD-associated pathways linked to cytokine signaling were significantly improved at weeks 4 and 16. Improvements in EASI, IGA, and the Pruritus Numeric Rating Scale were correlated with reductions in CCL13, CCL17, CCL22, CCL26, and periostin across all time points. After multiple testing correction and adjusting for sex and race as covariates, we identified the chemokine CCL26 as a pharmacodynamic marker for lebrikizumab response at weeks 4 and 16. Conclusions Selective inhibition of IL-13 with lebrikizumab monotherapy induced progressive inhibition of systemic biomarkers and pathways of type 2 inflammation, which correlated with clinical measures of improvement in patients with moderate-to-severe AD. Clinical Trial Registrations NCT04146363 and NCT04178967.